Is there a J-curve under COVID-19 effects. Issue 1 (2nd January 2023) - Ojaghlou, Mortaza; Uğurlu, Erginbay
ABSTRACT: Because of the outbreak of pandemic COVID-19, the economy and financial markets had a sharp decline. Also, based on the lockdown, we saw that amount of production and trade had decreased. This situation continues, and the effect on trade is still an important concern. In this paper, we investigate whether COVID-19 has an effect on trade by means of the real exchange rate in China-EU27 and China-USA. By using J-curve concept, for each trade partner, we use three models, which are ARDL, NARDL, and Multiplier NARDL, using three different data periods considering COVID-19. The results show that inverted J-Curve is proved with the long-run J-Curve effects for both partners, while COVID-19 makes factors favor J-Curve. Although J-Curve was inverted before the pandemic of COVID-9, during the COVID-19, we recognize the effect of J-Curve, which shows that the effect of real exchange rate on trade of China-EU27 and China-USA seems to favor China.